Dickens's Great expectations : Misnar's pavilion versus Cinderella - Meckier, Jerome (University Press of Kentucky, 2002)
Dickens scholar Jerome Meckier's acclaimed Hidden Rivalries in Victorian Fiction examined fierce literary competition between leading novelists who tried to establish their credentials as realists by rewriting Dickens's novels. Here, Meckier argues that in Great Expectations, Dickens not only updated David Copperfield but also rewrote novels by Lever, Thackeray, Collins, Shelley, and Charlotte and Emily Brontë. He periodically revised his competitors' themes, characters, and incidents to discredit their novels as unrealistic fairy tales imbued with Cinderella motifs. Dickens darkened his fa.